Effects of Fermented Radix puerariae Residue on Nutrient Digestibility and Reproductive Performance of Sows - Luo, Zhenfu; Zhao, Yuanyuan; Zeng, Liming; Yin, Jie; Zeng, Qinghua; Li, Xilong; He, Jianhua; Wang, Jing; Tan, Bi'e (Frontiers in Nutrition, 2021)
This study was conducted to investigate the effect of fermented Radix puerariae residue (FRPR) on reproductive performance, apparent total tract digestibility (ATTD) of nutrients, and fecal short-chain fatty acids (SCFAs) contents of sows. A total of 36 Landrace× Large White multiparous sows were randomly arranged into three treatments, representing supplementation with 0, 2%, and 4% FRPR to a corn-soybean meal and wheat bran-based diet during the whole gestation period. The results showed that dietary FRPR had no effects on litter size and the number of total alive piglets (P > 0.05). But the number of weaned piglets and weaning weight of litter were increased in sows of 4% FRPR treatment compared with control treatment (P < 0.05). Dietary 4% FRPR significantly decreased constipation rate, improved the ATTD of dry matter and organics, and the fecal contents of acetate, propionate, and total SCFAs (P < 0.05). In the offspring piglets, serum concentrations of total protein, alkaline phosphatase, IgG, IL-10, and TGF-β were increased but blood urea nitrogen content was decreased in 4% FRPR treatment (P < 0.05). There were no significant differences in all determined index except for fecal acetic acid and total SCFAs between control and 2% FRPR treatment (P > 0.05). These findings indicated that FRPR was used in the sow’s diets to show the positive effects on the fecal characteristics, utilization of nutrients, and reproductive performance. Maternal supplementation with 4% FRPR was recommended for improving immune responses, weaning litter size and litter weight of offspring piglets, which provides useful information for the application of residues of Radix puerariae.